Understanding bereaved parents and siblings : a handbook for professionals, family and friends - McQuaid, Cathy (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Understanding Bereaved Parents and Siblings is based on lived experiences and provides insight, ideas and inspiration on how to support the bereaved, how to talk to them about their experience and how to help people manage their own shock or grief. Part one of the book contains ten stories from parents and six from siblings sharing their experiences. Each narrator discusses their relationship with the person who died; what lead up to the death; the impact of the loss on the speaker; as well as what helped and what hindered them in their grief. Part two is aimed at professionals and draws on various topics such as grief and bereavement models, transgenerational loss, resilience, protection and creative ways of working with grief. The book will be an essential read for the bereaved and the professionals, family and friends who are supporting them"--
OCLC-licensed vendor bibliographic record.
Keywords: Parental grief; Grief in children; Bereavement -- Case studies; Bereavement in children -- Case studies; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Psychotherapy / Couples & Family